Pengaruh Pemberian Informasi Dan Diskusi Terstruktur Pada Perubahan Sikap Karyawan Terhadap Penggunaan Alat Pelindung Diri - Vembriati, Naomi; Wimbarti, Supra (Faculty of Psychology, Diponegoro University, 2015)
One of the factors causing high rates of workplace accidents is the human factor, i.e., the view that the use of Personal Protective Equipment (PPE) will cause the work discomfort and reduce the work speed so it will reduce the productivity. This attitude discourages employees to use PPE set by the company. This study was aimed to determine the effect of the provision of information and structured discussion on changes in employee attitudes towards the use of PPE. The design of experiment used in this research was multiple treatments and control with pretest, which involved two experimental groups and one control group. The first experimental group (EG1) was treated with the provision of information (academic detailing) and structured discussion. The second experimental group (EG2) received structured discussion without any provision of information. The control group (CG) was not given any treatment. The study involved 48 subjects, i.e. 16 people on EG1, 17 people on EG2, and 15 people in the CG. Statistical analysis using mixed ANOVA showed that there was a significant change in attitude towards the use of PPE (F=12.670; p<0.001) lead to more negative attitude. The research also found that there were no differences in attitudes toward the use of PPE among groups (F=1.178; p>0.05).